Strategi Komunikasi Dalam Pelaksanaan Program Corporate Social Responsibility (CSR) Oleh Human Resource (HR) PT. Sulotco Jaya Abadi Terdahap Komunitas Lokal di Kabupaten Tana Toraja - Ma'ruf Irwan Makkawaru (Journal of Communication Sciences (JCoS), 2020)
This study seeks to explore the communication strategy in implementing the Corporate Social Responsibility (CSR) program by Human Resource PT. Sulotco Jaya Abadi towards the local community in Tana Toraja Regency. The results show that the communication strategies used in the company's CSR program are as follows; initiatives that come from the company, by taking steps (1) first seeing the target of the communication process, (2) composing the message content (3) delivery with informative and educative methods. Then the second: initiatives based on community needs by conducting field observations with an approach through good communication. With this observation, it can be a consideration for companies to implement their CSR programs. The factors that influence the communication strategy in implementing CSR programs are the necessity factors, where the company sees what is needed by the surrounding environment then makes and designs it into a CSR program. The second factor is community development, where by carrying out this CSR program it is hoped that the surrounding environment can make good use of the program by providing education and understanding to the community. CSR program carried out by PT. Sulotco Jaya Abadi is a field that includes (1) the education sector and (2) the infrastructure sector.